2016
DOI: 10.1016/j.cl.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Recording concerns in source code using annotations

Abstract: A concern can be characterized as a developer's intent behind a piece of code, often not explicitly captured in it. We discuss a technique of recording concerns using source code annotations (concern annotations). Using two studies and two controlled experiments, we seek to answer the following 3 research questions: 1) Do programmers' mental models overlap? 2) How do developers use shared concern annotations when they are available? 3) Does using annotations created by others improve program comprehension and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…A concern is a piece of information about a code element, such as a feature it implements or a design decision [32]. Con-cernMapper [14] is both an Eclipse plugin and a framework to associate parts of programs with concerns, both through a GUI (graphical user interface) and an API (application programming interface).…”
Section: A Humanmentioning
confidence: 99%
“…A concern is a piece of information about a code element, such as a feature it implements or a design decision [32]. Con-cernMapper [14] is both an Eclipse plugin and a framework to associate parts of programs with concerns, both through a GUI (graphical user interface) and an API (application programming interface).…”
Section: A Humanmentioning
confidence: 99%
“…Automation of this task is, therefore, desirable and is part of on-going investigations. The easiest way should consist of asking the developer to decorate the code with meta-data about the piece of code that belongs to a particular application feature; similarly to what was done in [31,32]. This approach would help with the maintenance issue but it still requires some manual identification with all the problems this entails.…”
Section: Limitations and Open Challengesmentioning
confidence: 99%
“…Although in more realistic use cases, the number is expected to grow, it should not affect readability significantly. In controlled experiments [14], we showed that feature (and other concern) annotations are useful when shared with other developers -they improve program comprehension efficiency. Nevertheless, keeping annotations synchronized with source code changes could be challenging.…”
Section: Workflow Selectionmentioning
confidence: 99%
“…Concern annotations [12,14] are annotations acting as hints for developers, informing them about intentions behind a code element. Originally, they were intended to be inserted manually into the source code, preferably by programmers writing the code.…”
Section: Annotationsmentioning
confidence: 99%